Determinants of energy consumption: The case of African oil exporting countries - Akindele John Ogunsola; Christian Kakese Tipoy (Cogent Economics & Finance, 2022)
Persistent energy consumption issues are ascribed to the failure of energy planners to understand the various macroeconomic factors that influence energy consumption. Therefore, we investigated the factors influencing energy consumption in six net African oil-exporting countries (AOECs) between 1980 and 2018. Our contribution to the literature is the use of estimators; cross-sectional autoregressive distributed lag (CS-ARDL) and cross-sectional distributed lag (CS-DL) modelling approaches, which take into account the time dynamics, the heterogeneity of different countries and cross-sectional dependence, to explore the relationship between energy consumption and its major determinants, such as openness, economic structure and per capita income. The results revealed that per capita income did not impact significantly on energy consumption in AOECs during the period under study, while trade openness had a positive and significant effect on it. The third variable of interest, namely economic structure, had a negative and significant effect on energy consumption. These results led to various recommendation for policymakers and future research in the concluding section.
Keywords: F10; H10; H24; Q40; 330; trade openness; economic structure; per capita income; energy consumption; cross-sectional autoregressive distributed lag; cross-sectional distributed lag